Transparent Film Profiling and Analysis by White Light Scanning Interferometry - Hlaing, Nway Nway; Win, Lei Lei Yin; Tun, Hla Myo; Pradhan, Devasis (The Indonesian Institute of Science and Technology Research, 2024)
This paper describes the use of white light scanning interferometry with a Super luminescent diode (SLD) for thin film surface measurement. The technique provides 3D top surface and thickness profiles of transparent films, as well as detailed properties of multilayer film stacks, including material optical properties. The setup involves splitting a laser beam with a beam splitter, generating interference signals detected by a photodetector, and then converting analog signals to digital using an A/D converter for further analysis with LabView and MATLAB software. In this paper, the theoretical analysis and simulation study of white light scanning interferometry for transparent film measurement is discussed. This approach offers a flexible tool for both engineering and structured surface measurements.